The molecular genetics of Marfan syndrome and related disorders. Issue 10 (29th March 2006) - Robinson, P N; Arteaga-Solis, E; Baldock, C; Collod-Béroud, G; Booms, P; De Paepe, A; Dietz, H C; Guo, G; Handford, P A; Judge, D P; Kielty, C M; Loeys, B; et al.
Abstract : Marfan syndrome (MFS), a relatively common autosomal dominant hereditary disorder of connective tissue with prominent manifestations in the skeletal, ocular, and cardiovascular systems, is caused by mutations in the gene for fibrillin-1 ( FBN1 ). The leading cause of premature death in untreated individuals with MFS is acute aortic dissection, which often follows a period of progressive dilatation of the ascending aorta. Recent research on the molecular physiology of fibrillin and the pathophysiology of MFS and related disorders has changed our understanding of this disorder by demonstrating changes in growth factor signalling and in matrix-cell interactions. The purpose of this review is to provide a comprehensive overview of recent advances in the molecular biology of fibrillin and fibrillin-rich microfibrils. Mutations in FBN1 and other genes found in MFS and related disorders will be discussed, and novel concepts concerning the complex and multiple mechanisms of the pathogenesis of MFS will be explained.